Is Surgical Site Infection (SSI) after skin surgery affected by home municipal versus non-municipal water supply?. Issue 11 (November 2020) - Lee, Young; Ng, Diana; Goh, Maple; Hollewand, Clare; Locke, Michelle; Mathy, Jon A
Summary: Purpose: SSI represent one of the most common sources of morbidity and escalated healthcare costs in skin cancer management. It has been shown that exposing wounds to treated water does not increase SSIs, however a large proportion of Australasian patients reside in rural areas dependant on roof or bore collected water for their primary water supply, and no data exist regarding the association between tank water supply and SSI following skin surgery. Methodology: A nine-month retrospective analysis of patients undergoing skin cancer surgery at the Auckland Regional Plastic Surgery Unit was performed. Wounds assessed using a validated wound infection scoring system. Rates of SSI analysed against various clinical factors (water supply, smoking status, immunocompromise, glucose intolerance) and surgical factors (type of reconstruction, ulceration, lesion site, surface area of lesion). Results: 857 lesions were excised from 357 patients over the period studied. 718 lesions (83.7%) had municipal and 139 lesions (16.3%) had non-municipal water as their primary supply. Overall rate of clinically significant SSI was 15.6%, with no difference between municipal and non-municipal water groups (15.6% vs. 15.8% P = 0.946). Further subgroup analysis did not reveal any difference in rate of SSI based on type of surgical closure (direct closure, skin graft vs. flap). Conclusion: Non-municipal water supply was not associated with change in SSI relative to home municipal water supply in patients receiving skin cancer surgery. Our data supplements existing literature that water exposure does not influence SSI following skin surgery irrespective of primary home water supply.